Validation of FLIK-5 Innovative Teaching Materials Based on Local Wisdom to Encourage Creativity of Elementary School Students - Hasanah, Hasanah; Siahaan, Sardianto Markos; Tibrani, Masagus Mhd (Papanda Publisher, 2025)
Learning in elementary schools requires innovative teaching materials that foster students' creativity and instill a love for local culture. However, the teaching materials available are generally still general and have not raised the region's potential, so they do not support the development of creative thinking skills. This research aims to validate the innovative teaching materials FLIK-5 (Interactive Flipbook of Local Wisdom for Grade 5 Students), developed based on the local wisdom of Musi Banyuasin, especially on regional superior product materials. The superior products raised include gambo jumputan cloth, a typical handicraft of the Musi Banyuasin community. The research uses a research and development (R&D) approach with the ADDIE model at the expert validation stage. The research subjects comprised five validators: material experts, media experts, and linguists. Data was collected using a validation sheet that assessed the feasibility aspects of content, appearance, language, and linguistics, then analyzed in a quantitative descriptive manner. The validation results showed that FLIK-5 obtained the